Ghana’s Preparedness Now and For Future Pandemics - Akligoh, Harry (My University, 2020)
The future of nations in the face of the rampaging effect of the COVID-19 is undoubtedly hinged on their capacity to test, trace and treat. That notwithstanding, the COVID-19 pandemic came as a surprise to most nations globally but most importantly countries in Africa whose health systems are fragile and not robust enough to handle occurrences like COVID-19. Presidents of Nations in times like this are developing preparedness strategies of which Ghana is not left out. During the 8th presidential address to the nation, the president highlighted some key government plans though laudable, I took some turns to the plan and made some recommendations within this article on what the Government of Ghana should be focusing on as Ghana's preparedness plan now and for handling future pandemics.
Keywords: COVID-19; Ghana; Healthcare system; Laboratories; Preparedness